EISCAT observations of plasma patches at sub-auroral cusp latitudes - J. Moen; H. C. Carlson; K. Oksavik; C. P. Nielsen; S. E. Pryse; H. R. Middleton; I. W. McCrea; P. Gallop (Annales Geophysicae, 2006)
A sequence of 3 patches of high-density (10 12 m −3 ) cold plasma on a horizontal scale-size of 300–700 km was observed near magnetic noon by the EISCAT VHF radar above Svalbard on 17 December 2001. The patches followed a trajectory towards the cusp inflow region. The combination of radar and all-sky observations demonstrates that the patches must have been segmented equatorward of the cusp/cleft auroral display, and hence their properties had not yet been influenced by cusp particle showers and electrodynamics on open flux tubes. The last patch in the sequence was intersected by radio tomography observations, and was found to be located adjacent to a broader region of the same high electron density further south. The patches occurred under moderately active conditions (Kp=3) and the total electron content (TEC) of the high-density plasma was 45 TEC units. The train of patches appeared as a segmentation of the tongue of ionization. The sequence of patches occurred in association with a sequence of flow bursts in the dusk cell return flow. It is proposed that reconnection driven pulsed convection is able to create sub-auroral patches in the region where high density mid-latitude plasma is diverted poleward toward the cusp. It is the downward Birkeland current sheet located at the equatorward boundary of the flow disturbance that represents the actual cutting mechanism.